Fixed-time consensus of heterogeneous multi-agent systems based on distributed observer. Issue 9 (4th July 2021) - Sun, Fenglan; Liu, Peiyong; Li, Hao; Zhu, Wei
Abstract : Fixed-time consensus of the heterogeneous multi-agent system, which consisting of first-order and second-order agents with a leader, is studied in this paper. A new control algorithm based on the distributed observer is proposed. By adopting the graph theory, matrix theory, control theory and Lyapunov stability method, some sufficient conditions for the fixed-time consensus and an upper bound of settling time are given. An example is presented to illustrate the potential correctness of the main results.